(untitled) - Kramsch, Claire (Oxford, 2000)
This book investigates the close relationship between language and culture. It explains key concepts such as social context and cultural authenticity, using insights from fields which include linguistics, sociology, and anthropology.
Keywords: Language and languages; Study and teaching,Foreign speakers